ALLEVIATIVE EFFECT OF GINGEROL ON CELL MEDIATED AND HUMORAL IMMUNITY AND IMMUNE ORGANS AGAINST PENICILLIC ACID MYCOTOXICOSIS IN BROILER CHICKENS: Life Sciences-Veterinary Science - N.PAZHANIVEL; C.BALACHANDRAN; B.MURALIMANOHAR; G.DHINAKARRAJ; V.BALAKRISHNAN; J.JOHN KIRUBAHARAN; A.RAJA (International Journal of Life Science and Pharma Research, 2022)
80 days-old broiler chicks obtained, 72 were randomly allotted to six groups of 12 chicks each with diets of [(T1-control, T2- Gingerol (0.1%), T3- Gingerol (0.2%), T4- Penicillic acid (15 ppm), T5- Penicillic acid (15 ppm) + gingerol (0.1%), T6- Penicillic acid (15ppm) + gingerol (0.2%)] from 0 to 28 days of age. Remaining eight chicks were used as no toxin, no gingerol and no vaccine group (T7). Two birds from each group were sacrificed on 7th, 14th, 21st and 28th day of age for Cell Mediated Immunity (CMI) assay. Remaining birds were sacrificed (28th day) to study the effect on growth, pathological changes in lymphoid organs and immune status. There was a highly significant (P<0.01) decrease in the splenic lymphocyte stimulation index values of T4 and T5. Highly significant (P<0.01) increase in the CMI was observed in T6 group when compared to T4 group. Histopathological examination in the T4 group revealed mild to moderate lymphoid cell depletion and mild to moderate lymphoid cell depletion in the bursa of Fabricius. T2 group revealed mild medullary lymphoid cell depletion in a few follicles, lymphocytolysis and apoptosis in the bursa of Fabricius, thinning of cortex in thymus and plasma cell depletion in Harderian gland. T5 group revealed moderate lymphoid cell depletion in the bursa of Fabricius. T6 group revealed cystic changes in the follicles of the bursa of Fabricius. Inclusion of gingerol at 0.2% level alleviated the effect on cell mediated immunity against penicillic acid mycotoxicosis (15 ppm) in broiler chickens.